Case Report: Tadpole pupil and concurrent migraine in an adolescent patient is a novel correlation - Scheid, Alexander; Gammelgaard Henneberg, Rebecca Lise; Hansen, Jonas Kjeldbjerg (Frontiers in Pediatrics, 2024)
Background: Tadpole pupil is a rare phenomenon characterized by brief and irregular deformation of the pupil caused by segmental contraction of the iris dilator muscle. It is most prevalent in adult women and is, in these cases, often associated with migraine.We present the unique case of a 16-year-old girl that debuted with recurrent episodes of tadpole pupil and vestibular migraine. This association has never been demonstrated in pediatric patients before. During thorough clinical examination a thyroid carcinoma was found which due to its localization is not causative to the tadpole pupil and considered an incidental finding.The association between migraine and tadpole pupil, not previously described in pediatric patients, adds to the demographics of tadpole pupil. A possible pathophysiological link between the two conditions is discussed, but further research is needed to enlighten the pathophysiology behind it.